ANALYSIS OF FOOD COST CONTROL AT THE ONE LEGIAN HOTEL - I Wayan Arya Pradiptha; Lien Darlina; Ida Ayu Elistyawati (Journal of Applied Sciences in Travel and Hospitality, 2018)
This study focuses on food costs controlling with special reference to the hospitality industry. The purpose of this research is to know the control of food cost at The ONE Legian Hotel in May, June, July 2017, and to identify the cause of food cost percentage’s variance between actual food cost and standard food cost. This research uses two methods of data analysis : 1) Quantitative method is use to determining the variance between the standard with actual food cost reconciliation, and calculating variance by using the one way methods analysis which refers to Mulyadi (1995 : 425) to know the profit or loss that caused by the variance, 2) Qualitative descriptive method by giving interpretation about data of standard and actual food cost reconciliation. Data collection method in this research are interview, observation, documentation review, literature review. The results of this research indicate that: (1) food cost controlling at The ONE Legian Hotel in May and June has been run well, but in July the implementation did not run well, this is indicated from the happening of the adverse variance between actual food cost with standard food cost, (2) an increase of the food cost reconciliation’s percentage between the actual from standard budgeted in May, June and July due to an increase in total incoming stocks, gross consumption and net consumption, beside that, the increase in food cost percentage also caused by the decrease of total opening inventory, total inventory available, total closing inventory, or decrease of elements of food adjustment, and net food sales.